Cr(VI) removal from soils and groundwater using an integrated adsorption and microbial fuel cell (A-MFC) technology. (September 2019) - Zhang, Tingting; Hu, Liyang; Zhang, Minglu; Jiang, Mengyun; Fiedler, Heidelore; Bai, Wenrong; Wang, Xiaohui; Zhang, Dayi; Li, Zetang
Abstract: Remediation of hexavalent chromium [Cr(VI)] has been widely studied for its high mobility and toxicity. As Cr(VI) migrates in natural environment, both soils and groundwater are contaminated simultaneously. In the present study, a novel reactor combining adsorption and microbial fuel cell (A-MFC) using Platanus acerifolia leaves was developed for removing Cr(VI) from groundwater and soils. When initial Cr(VI) concentration was 50 mg/L, the adsorption efficiency of A-MFC achieved 98% after 16 h. Afterwards, the leaves were used for fabricating an MFC-integrated leaching reactor. The A-MFC significantly improved the overall Cr(VI) removal efficiency through leaching and 40% of Cr(VI) in the soil column was removed. The electrical voltage and current of A-MFC reactor achieved averagely 343 mV and 141 μA to maintain the system operation without extra energy supply. This novel A-MFC reactor is an environmentally friendly technology which achieved efficient Cr(VI) removal from groundwater and soils using natural materials, proving the concept that integrated self-remediation of Cr(VI) in contaminated soil and groundwater with natural material and energy. Graphical abstract: Image 1 Highlights: First biomaterial combined adsorption and microbial fuel cell (A-MFC) reactor. Cr(VI) removal and reduction by A-MFC reactor from soil and groundwater. High adsorption capacity of green waste Platanus acerifolia leaves.